Metallic copper spray: a new control technique to combat invasive container-inhabiting mosquitoes - Becker, Norbert; Oo, Thin Thin; Schork, Nino (Parasites & vectors, 2015)
The control of container-inhabiting mosquitoes is mainly based on environmental management with special emphasis on community participation e.g. source reduction by elimination or modification of water bodies. However, citizens are often not aware of the problems related to urban mosquito control or just ignore the advice provided during anti-mosquito control campaigns. In particular, cemeteries contain favourite breeding sites for container-inhabiting mosquitoes like Ochlerotatus j. japonicus, Culex pipiens s.l./Cx. torrentium, Aedes aegypti or Aedes albopictus. In our study, we investigated whether metallic copper e.g. in form of copper spray can be a suitable and cost-effective tool to combat mosquito breeding in vases or other similar small containers where no commonly used insecticides can be applied.